A novel strategy for realising environmentally friendly pigment foam dyeing using polyoxyethylene ether surfactant C14EO5 as a foam controller. (24th March 2017) - Chen, Shaoyu; Wang, Chaoxia; Fei, Liang; Liu, Hongbing
Abstract : Development of an environmentally friendly pigment dyeing process with excellent colour depth and levelness is an effective strategy for solving pollution problems in traditional dyeing. A functional polyoxyethylene ether nonionic surfactant, tetradecyl alcohol polyoxyethylene ether with an EO chain length of 5 (C14 EO5 ), was used as a foam controller, namely a foaming agent and foam stabiliser, in the pigment foam dyeing process. The foamability and the foam stability of C14 EO5 were tunable by adjusting its concentration. The foaming ratio and the foam half‐life of C14 EO5 were 5.22 and 32.21 min, respectively, at a concentration of 8 wt%. The addition of pigment dispersion (ranging from 1 to 6 wt%) slightly affected the foaming ratio and the foam half‐life owing to the interplay of increased viscosity and pigment particle destabilisation. After the influences of binder on foam properties of C14 EO5 were investigated, the concentration of binder and the stirring time for foaming were determined as 15 wt% and 7 min respectively. Owing to the stable foaming ratio and foam half‐life of the pigment foam dyeing dispersion, the colour depth of dyed cotton fabric was tailored solely by changing the dosage of pigment dispersion. Furthermore, the dyed cotton fabric showed not only a high K / S value but also perfect colour levelness and fastness. These results demonstrate that the pigment foam dyeing process with a foam controller, C14 EO5, reduces chemical and water consumptions, as well as improving the colour depth and levelness. This represents a significant step forward as regards environmentally friendly pigment dyeing.